Partition Dimension of Complete Multipartite Graph - Safriadi Safriadi; Hasmawati Hasmawati; Loeky Haryanto (Department of Mathematics, Hasanuddin University, 2020)
Determining a resolving partition of a graph is an interesting study in graph theory due to many applications like censor design, compound classification in chemistry, robotic navigation and internet network. Let and , the distance between an is . For an ordered partition of , the representation of with respect to is . The partition is called a resolving partition of if all representation of vertices are distinct. The partition dimension of graph is the smallest integer such that has a resolving partition with element.In this thesis, we determine the partition dimension of complete multipartite graph , which is limited by , with and . We found that , , and , .